Experimental Investigation about the Parameters that Effect on Evap-oration from Sub-storage Reservoir - M. Abdulhameed, Isam; Hatem Kamelb, Ammar; Ibraheemc, Sura (Anbar Journal of Engineering Sciences, 2018)
Management of water resources become one of the most important subjects in the human’s life. The water sustains life on earth, therefore; more care for water management is necessary. In the last years, studies show water use will be more in the world as result of rapid increase in population, industrialization, and urbanization etc. The evaporation losses from dam’s reservoirs and lagoon form very huge losses in water resources. The annual evaporation depth losses in Iraqi Western Desert is about (2.25 -3) meter, this depth store the highest percentage of the small dams. Sub-surface storage reduces evaporation losses and maintains water quality by minimizing salt concentration. In present study, three tanks are used to simulate the subsurface reservoirs to study the effectiveness of underground storage on reducing the evaporation loss. Each tank have squares cross section tanks of (80) cm length and (40) cm depth and filled up to (34) cm with different graded soil (labeled as A, B with coarse soil, and D with fine soil) to simulate the storage below the ground. While the forth tank filled with water (labeled as C) to represent the reservoir of direct evaporation for comparison study. The present study considers three parameters that can controlled the evaporation from subsurface reservoirs: (a) temperature variation, (b) water table variation, and (c) material properties such as porosity. The field study continues for four months, it was started at Jun.11, 2016 and ended at Dec. 15, 2016 in the Erbil city at north of Iraq. The results showed evaporation losses are reduced by using subsurface storage reservoir with gravel in comparison with free surface evaporation. The evaporation losses are reduced about 46 % , 39% , 64% when the water table below gravel surface range from 5 to 10 cm , while at 20 cm depth of the water table the evaporation reduction is about (85 % to 86% 95%) from A, B and D tanks with porosity 0.65 ,0.67 and o.35 for A ,B and D tanks, respectively..